Expression of surface hydrophobic proteins by Candida albicans in vivo. - Glee, P M (1995)
Candida albicans modulates cell surface hydrophobicity during growth and morphogenesis in vitro. To determine if surface hydrophobicity is expressed during pathogenesis, we generated a polyclonal antiserum against yeast hydrophobic proteins. The antiserum was then used for indirect immunofluorescence analysis of tissues from mice colonized and chronically infected with C. albicans. Results demonstrated that yeast hydrophobic proteins are exposed on fungal cells present in host tissues. The polyclonal antiserum distinguished between hydrophobic and hydrophilic cell surfaces in vitro and gave similar staining patterns and intensities for C. albicans cells in vivo. Of the yeast forms present within tissue lesions, approximately half exhibited moderate to intense immunofluorescence with the antiserum. Immunoblot analysis indicated that antigens recognized by the antiserum are predominantly low-molecular-mass hydrophobic proteins that are expressed by different C. albicans isolates and are expressed regardless of growth temperature. Taken together, the immunofluorescence and immunoblot analyses of antigens indicate that C. albicans displays surface hydrophobic proteins during pathogenesis and these proteins are available for hydrophobic interactions with host tissues. The effect of hydrophobic protein exposure on the virulence of C. albicans is discussed.